2021
DOI: 10.1001/jamadermatol.2021.0025
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Crizotinib Treatment in a Patient With Unresectable GOPC-ROS1 Fusion Agminated Spitz Nevi

Abstract: We thank the patient's parents for granting permission to publish this information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…The use of crizotinib-targeted therapy (280 mg/m 2 twice daily) was reported in a 30-month-old girl with unresectable ASN and known GOPC-ROS1 kinase fusion. 3 Complete flattening of the periocular, scalp, and auricular lesions to faintly pigmented macules was achieved after 20 weeks of treatment. Crizotinib was well tolerated, apart from mild nausea and vomiting, but a nasogastric tube was required for drug administration, and lesions reappeared gradually following treatment.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The use of crizotinib-targeted therapy (280 mg/m 2 twice daily) was reported in a 30-month-old girl with unresectable ASN and known GOPC-ROS1 kinase fusion. 3 Complete flattening of the periocular, scalp, and auricular lesions to faintly pigmented macules was achieved after 20 weeks of treatment. Crizotinib was well tolerated, apart from mild nausea and vomiting, but a nasogastric tube was required for drug administration, and lesions reappeared gradually following treatment.…”
Section: Discussionmentioning
confidence: 95%
“…Our literature review identified several procedural and pharmacologic interventions for ASN, including surgical excision with or without a skin graft, electrodesiccation, cryotherapy, and the use of crizotinib, a multitargeted tyrosine kinase inhibitor. 3 , 4 The undertaking of nonsurgical techniques such as cryotherapy of Spitzoid melanocytic neoplasms rests on accurate diagnosis and exclusion of similar neoplasms that have uncertain or malignant biologic behavior, such as Spitz tumors and Spitzoid melanomas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NTRK1/2/3 gene rearrangements, which are found at a reasonable frequency in pediatric tumors but are exceptionally rare in adults, are associated with the tumor's responsiveness to entrectinib or larotrectinib [105][106][107][108]. ALK, ROS1 and RET rearrangements, although not formally classified as agnostic markers, occur in multiple tumor types and render sensitivity to appropriate inhibitors [63,[109][110][111][112]. HER2 amplification accompanied by gene overexpression may also be considered as an example of a more or less agnostic druggable event [113][114][115].…”
Section: Agnostic Versus Tissue-specific Targetsmentioning
confidence: 99%